(6x-3)2=(4x+7)3

Simple and best practice solution for (6x-3)2=(4x+7)3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x-3)2=(4x+7)3 equation:


Simplifying
(6x + -3) * 2 = (4x + 7) * 3

Reorder the terms:
(-3 + 6x) * 2 = (4x + 7) * 3

Reorder the terms for easier multiplication:
2(-3 + 6x) = (4x + 7) * 3
(-3 * 2 + 6x * 2) = (4x + 7) * 3
(-6 + 12x) = (4x + 7) * 3

Reorder the terms:
-6 + 12x = (7 + 4x) * 3

Reorder the terms for easier multiplication:
-6 + 12x = 3(7 + 4x)
-6 + 12x = (7 * 3 + 4x * 3)
-6 + 12x = (21 + 12x)

Add '-12x' to each side of the equation.
-6 + 12x + -12x = 21 + 12x + -12x

Combine like terms: 12x + -12x = 0
-6 + 0 = 21 + 12x + -12x
-6 = 21 + 12x + -12x

Combine like terms: 12x + -12x = 0
-6 = 21 + 0
-6 = 21

Solving
-6 = 21

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 3x=5(x-6) | | 27+u=3-3u | | 2(5+x)=150 | | 7-1x=4+x | | x^4-9x^3+27x^2-15x-52=0 | | X=45-4x | | 7-x+2=2x-12 | | 9x^2+17=71 | | 0=8t | | -x^2+9x=18 | | 6x^2-12x=-1 | | -7x=2x+3 | | 3m-2=-5m+9 | | x-8.8=-6.9 | | -6x+24=18 | | 15X+100000=14x+200000 | | 2b+6a=14 | | 4(x)-24=-20 | | 3(x-3)=-6 | | -x^2+11x=18 | | 3a+4b-5c=0 | | 4k^2+12k+9=0 | | -5x+17=-2x-4 | | p+31=13 | | 9v-5v=44 | | 3x-3=100 | | -2x+24=14 | | x+23=-14 | | -3x+1=-6x+2 | | Z^2+12z+36=0 | | -(x-8)=3 | | 2b^2-9b-5=0 |

Equations solver categories